FUNDAMENTALLY SPEAKING. - Leland, Richard W. (ETC: A Review of General Semantics, 2025)
The article explores how fundamental concepts of language remain essential for understanding human individuality, social structures, and the workings of the mind. Topics include the enduring significance of linguistic fundamentals in shaping human thought and society; the methodological challenges of using language to analyze itself; and the interpretation of Aristotle's treatises, emphasizing his aim to illuminate rhetoric and poetry rather than showcase personal mastery.